Kontribusi Pemikiran Modern terhadap Reformasi Pendidikan Islam - Musthofa, Fu’ad Zaky; Baidi, Baidi (Lembaga Yasin AlSys, 2025)
Islamic education serves as a fundamental pillar in shaping the character and intellect of the Muslim community; however, its traditional system often struggles to address the challenges posed by globalization and technological advancement. This article aims to examine the contribution of modern thought to the reform of Islamic education, particularly in the areas of curriculum development, teaching methods, and educational objectives. A literature-based approach was employed, analyzing the ideas of modern Islamic thinkers alongside contemporary practices in Islamic education. The analysis reveals that modern thought promotes the integration of religious and secular knowledge within the curriculum, the implementation of interactive and critical teaching methods, and the expansion of educational goals to include 21st-century competencies. This approach enables Islamic education to cultivate a generation that is not only religious but also capable of analytical thinking, creativity, and adaptability in the face of global change. Such reforms enrich the Islamic education system, making it more inclusive, contextual, and empowerment-oriented. Nonetheless, cultural resistance and limited resources remain significant challenges, necessitating collaboration among various stakeholders. Therefore, modern thought plays a strategic role in shaping an Islamic education system that is relevant, progressive, and responsive to contemporary demands.